Penerapan Analisis SWOT Jangka Pendek pada Pesantren Udara 14.2690 MHz. - Kurniawan, Luqman (Tanzhim: Jurnal Dakwah Terprogram, 2024)
Every organization is required to create strategies in various forms to respond to changes in internal and external situations and conditions so that organizational goals are achieved. SWOT analysis is a method often used by organizations to understand conditions and formulate strategies. SWOT analysis was born and developed to formulate macro and long-term oriented strategies. Meanwhile, da’wah organizations in carrying out their da’wah activities are often faced with specific, tactical and short-term problems among the people. This article aims to describe the process of applying SWOT analysis in formulating a short-term da'wah strategy based on the guardian pilgrimage activities by Pesantren Udara 14.2690 MHz. This research approach is descriptive qualitative. Data comes from interviews, observations and literature. The analysis process uses strategy formulation theory, especially SWOT analysis. Research results: First, in carrying out internal and external mapping, strategic factors are limited by the scope of strategic objectives and issues. Second, the SWOT identification process is carried out by evaluating conditions and testing each strategic factor by integrating the strategic factors. Third, in the matching process you don't really have to have straight pairs of internal and external pairs. Alternative strategies can emerge from several internal and external strategic factors. Fourth, strategy formulation in the form of specific technical solutions that are integrated between short-term strategies in the guardian pilgrimage activities of the Pesantren Udara 14.2690.